Proceso De Comercialización Y Su Relación Con Los Planes De Desarrollo De La Empresa Pública Municipal De Saneamiento Ambiental De Babahoyo (EMSABA-EP) - Burgos Junco, Celia María (2015)
The thesis with the theme "marketing process and its relationship to the development plans of the Municipal Public Utility Environmental Sanitation Babahoyo (EMSABA-EP)", aimed to determine the level of efficiency and effectiveness of the marketing process in relation with the development plan EMSABA-EP, scientifically arguing both variables, the first defines the steps in the marketing area determined levels of staff productivity and the second as instruments of progress of the company, the methodology was Bibliographic and field with a population of 16,485 universe external customers, 145 employees and 12 managers types, applying the sample is working with external customers 72 296 employees and 6 managers. The results conclude that the process is not meeting customer demands, there is ignorance on the part of employees of the development plan, the same that is not socialized with the entire staff, area marketing company does not cover the use of marketing strategies, allowing some impact on Babahoyense assertive community. The proposed as an alternative in the research is the development of a marketing plan with marketing approach that will raise the level of efficiency and effectiveness of the administrative management of the Municipal Public Utility Environmental Sanitation Babahoyo (EMSABA-EP) approach that aims to optimize the activities of the company and improve their level of labor productivity.